Media Islam dan Kesalehan Publik: Kajian terhadap Ragam Cetakan Al-Qur'an Kontemporer di Indonesia - Fitriatus Shalihah (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2021)
Along with the rapid advancement of technology, the dynamics of the Qur'an print in Indonesia develops significantly. This can be seen from the emergence of various kinds of Qur’an printing. Publishers introduce interesting innovations that suit the needs of readers and learners of the Qur'an. This phenomenon cannot be separated from the globalized online market. However, media and Islamic relations in this case are not only related to market place and the consumptive cultural structure of society, but also as a form of mediation of public piety. For this reason, this study aims to answer these questions: why the use of media in the printing of the Qur'an encourages the formation of public piety in Indonesia? How is the space of public piety built by the existence of the media, especially in contemporary Qur'an printing? This article is a bibliographic study with descriptive methods of analysis. The result of this paper is that the printing of the contemporary Qur'an in Indonesia has mediated Islamic umma to be pious people because it is designed based on the needs of each Muslim, thus encouraging them to learn the Qur’an and implement its teachings, such as the Qur'an for women, the braille Qur'an, the Qur'an for kids, al-Qur'an travel, al-Qur'an tajwid, and some are packed with sticker designs to be pasted on the windshield of vehicles and walls of the room.